Inflow Occlusion Combined With Bleomycin Sclerotherapy for Management of Macro/Mixed Cystic Lymphatic Malformation in Children - Han, Tao; Ji, Yi; Cui, Jie; Shen, Weimin (Frontiers in Pediatrics, 2021)
Background: The link between cystic lymphatic malformation (cLM) and normal lymphatic system has become the focus of research. This study aimed to assess the outcomes of indocyanine green (ICG) lymphography-guided inflow occlusion combined with bleomycin sclerotherapy for the management of macro or mixed cLM in children. Methods: Between June 2018 and October 2020, inflow occlusion combined with bleomycin sclerotherapy was performed in 81 cLM patients (age range from 6 months to 8 years). All cases were evaluated by the following parameters: cLM location, histological typing, number of afferent lymph vessels, dermal backflow, curative effects, treatment frequency, and postoperative complications. The duration of postoperative follow-up was from 10 to 16 months. Results: All cLM cases could be found with at least one lymphatic inflow. Excellent outcomes were observed in 68 cases (84.0%), 11 cases (13.6%) experienced good outcomes, and two (2.5%) cases had fair outcome. No case experienced repeated treatment for more than three times. Wound infection, fever, and scar hyperplasia were the independent adverse events, which were managed by symptomatic treatment. Conclusion: Inflow occlusion combined with bleomycin sclerotherapy renders a safe and efficient approach for the management of macro or mixed cLM.